Consumo de carbohidratos en el paciente diabético y su relación con el rol educativo del personal de enfermería. Centro la isla, parroquia San Cristóbal, Quevedo, período septiembre 2017 – febrero 2018. - Montiel Tomalá, Mabel Alicia (2018)
Diabetes is a disease that can cause complications in different parts of the body and increase the risk of premature death. That is the reason to carry out scientific research constantly according to the environment. The present study is focused on determining if the educational role of the nursing staff at Centro de Salud La Isla from San Cristóbal urban parish, Quevedo canton is related to the inadequate carbohydrate intake of the diabetic patient. Empirical, probabilistic, and field methods were used. In addition, they were supported by data collection techniques such as surveys and interviews in order to get information related to the educational role of nursing staff and its incidence in relation to the dietary habits of diabetic patients which are in treatment at this medical center; specifically the group of high carbohydrates, medium, and low glycemic index. Despite being known that the consumption of sugars affects their health, a considerable percentage of them consume it in limited measures without becoming worrying. It is detected that the work of nursing is more oriented to the assistance than to the educational aspects and training work of patients, so there is a staff’s tendency to improve knowledge for performing their activities and improving their performance. The application of the educational strategies of promotion, prevention, and care guide will permit the nursing staff to contribute and improve the lifestyle of diabetic patients at Centro de Salud La Isla.